N‐3 Polyunsaturated Fatty Acids: Relationship to Inflammation in Healthy Adults and Adults Exhibiting Features of Metabolic Syndrome. Issue 4 (1st March 2013) - Robinson, Lindsay E.; Mazurak, Vera C.
Abstract: Individuals with metabolic syndrome (MetS) have a higher risk of type 2 diabetes and cardiovascular disease, therefore, research has been directed at reducing various components that contribute to MetS and associated metabolic impairments, including chronic low‐grade inflammation. Epidemiological, human, animal and cell culture studies provide evidence that dietary n‐3 polyunsaturated fatty acids (n‐3 PUFA), including alpha‐linolenic acid (18:3n‐3, ALA), eicosapentaenoic acid (20:5n‐3, EPA) and/or docosahexaenoic acid (22:6n‐3, DHA) may improve some of the components associated with MetS. The current review will discuss recent evidence from human observational and intervention studies that focused on the effects of ALA, EPA or DHA on inflammatory markers in healthy adults and those with one or more features of MetS. Observational studies in healthy adults support the recommendation that a diet rich in n‐3 fatty acids may play a role in preventing and reducing inflammation, whereas intervention studies in healthy adults have yielded inconsistent results. The majority of intervention studies in adults with features of MetS have reported a benefit for some inflammatory measures; however, other studies using high n‐3 fatty acid doses and long supplementation periods have reported no effect. Overall, the data reviewed herein support recommendations for regular fatty fish consumption and point toward health benefits in terms of lowering inflammation in adults with one or more features of MetS.